Tasawuf antara al-Ghazali & Ibnu Taimiyah - Muhammad Sayyid Ahmad,'Abd al-Fatah; Anasy, Muhamad Muchson (Jakarta : KHALIFA, 2005)
Sufism; Ghazzali, 1058-1111; Ahmad ibn'Abd al-Halim Ibn Taymiyah, 1285 or 4; Islamic philosophy; comparative study
Keywords: al-Ghazzali, -- 1058-1111 -- Views on Sufism; Ibn Taymiyah, Ahmad ibn'Abd al-Halim, -- 1263-1328 -- Views on Sufism; Sufism